A case series of COVID‐19 patients with chronic hepatitis B virus infection. Issue 11 (14th July 2020) - Li, Yang; Li, Chunyang; Wang, Jian; Zhu, Chuanwu; Zhu, Li; Ji, Fang; Liu, Longgen; Xu, Tianmin; Zhang, Biao; Xue, Leyang; Yan, Xiaomin; Huang, Rui; et al.
Abstract: Previous studies reported that coronavirus disease 2019 (COVID‐19) was likely to result in liver injury. However, few studies reported the impacts of COVID‐19 on liver function in patients with chronic liver diseases. We aimed to describe a case series of COVID‐19 patients with chronic hepatitis B virus (HBV) infection. Confirmed hospitalized COVID‐19 patients from hospitals in 10 cities of Jiangsu province, China, were retrospectively included between 18 January 2020 and 26 February 2020. Demographic information, epidemiologic data, clinical features, and treatment data were extracted from medical records. Seven COVID‐19 patients with chronic HBV infection were included. Six (85.7%) patients were male. The patients aged from 33 to 49 years. Two patients had HBV‐related cirrhosis. One patient (14.3%) was positive for serum HBV e‐antigen. On admission, 1 (14.3%) patient had mildly elevated alanine aminotransferase (ALT) level (>40 U/L) and 1 (14.3%) had elevated aspartate aminotransferase (AST) level (>40 U/L). The serum albumin level and platelet counts were decreased in two patients with HBV‐related liver cirrhosis. Three (42.9%) patients had elevated ALT level and 2 (28.6%) patients had elevated AST level in hospitalization. However, the peak ALT and AST level during hospitalization was 51 U/L and 44 U/L, respectively. As of 29 February 2020, all patients were discharged. No patient was admitted to the intensive care units or developed liver failure during hospitalization. The abnormalities of liver function are not uncommon on COVID‐19 patients with chronic HBV infection in our case series. However, no patient developed severe liver‐related complications during hospitalization. Highlights: The impacts of COVID‐19 on liver function in patients with chronic hepatitis B remain unclear. Our study showed the clinical features of COVID‐19 with CHB by a multicenter cohort. About half of patients presented mild elevated ALT and AST level. The abnormalities of liver function are common on COVID‐19 patients with CHB.